Study of the Average Elapsed Time for Head Trauma Patients from the Accident until Transportation to Hospital and Commencement of Diagnostic and Therapeutic Treatment - Seyyed Mohammad Rakei (پزشکی بالینی ابن سینا, 2002)
Accident and crashes are major causes of mortality in today’s society. In approximately one half of the cases of death are following trauma and head injuries. In cure and recovery of patients , the elapsed time from the accident till the arrival of the patient and the start of medical procedures has a significant role. This survey has been conducted in order to determine the average elapsed time in relation to head injury patients from the time of the accident until arrival at the Mobasher Kashany hospital of Hamadan and beginning of diagnostic and therapeutic treatment.